2017
DOI: 10.4155/tde-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

Stratum Corneum Modulation By Chemical Enhancers and Lipid nanostructures: Implications for Transdermal Drug Delivery

Abstract: Skin is the outermost and largest protective covering of the body. The uppermost layer of the skin, stratum corneum also called the horny layer is composed of keratin-filled cells covered by a lipid matrix which shields the skin from physical and chemical entrants. The lipid lamellar structure comprises of ceramides, cholesterol, fatty acids and proteins. Chemical enhancers that mimic the lamellar chemistry, reversibly fluidize the latter can be utilized for enhancing transport of cargo across the epidermis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…The most established and less invasive methods for enhanced drug penetration through the skin barrier involve either removal of outermost skin layer achieved by the peeling tape (tape stripping) or usage of various chemical enhancers, such as dimethylsulphoxide, propylene glycol, ethanol, oleic acid, EDTA, sodium glycocholate and related cholates, Tween 20 (a non-ionic polysorbate surfactant), Brij 35 (polyoxyethylene lauryl ether), saponins, and bile salts [75][76][77]. Generally, penetration enhancers are small molecules that temporarily soften the bond between the adjacent cells of the corneal epithelium (EDTA) or increase the fluidity of membranes (cholates) [76]. It was demonstrated that chemical enhancers can increase dermal penetration of various antifungal drugs.…”
Section: Physical and Chemical Strategies To Enhancement Of Intra-andmentioning
confidence: 99%
“…The most established and less invasive methods for enhanced drug penetration through the skin barrier involve either removal of outermost skin layer achieved by the peeling tape (tape stripping) or usage of various chemical enhancers, such as dimethylsulphoxide, propylene glycol, ethanol, oleic acid, EDTA, sodium glycocholate and related cholates, Tween 20 (a non-ionic polysorbate surfactant), Brij 35 (polyoxyethylene lauryl ether), saponins, and bile salts [75][76][77]. Generally, penetration enhancers are small molecules that temporarily soften the bond between the adjacent cells of the corneal epithelium (EDTA) or increase the fluidity of membranes (cholates) [76]. It was demonstrated that chemical enhancers can increase dermal penetration of various antifungal drugs.…”
Section: Physical and Chemical Strategies To Enhancement Of Intra-andmentioning
confidence: 99%
“…Another physical enhancement technology is the Microneedles (MN) one; this technology employs micrometric size needles to pierce the epidermis and deliver the drug directly in the vascularized layers [102,103]. Chemical enhancement instead consists of adjusting the drug formulation by adding appropriate chemical substances that cause the swelling of skin barrier [104]. A further skin penetration enhancement strategy consists of the incorporation of the active substance into nanocarriers; such devices can be designed in order to possess physical and chemical properties that allow them to drive the drug across the skin barrier to reach the systemic circulation without affecting the outer skin integrity [105,106].…”
Section: Skin Interaction With Drugs and Current Challenges In Dermentioning
confidence: 99%
“…In the work of Pereira [123] adapalene (logP = 8.5) loaded PCL nanocapsules were produced and topically applied: the high hydrophobicity of both carrier and drug facilitated diffusion in the SC but no further penetration was observed, making the system suitable for topical administration. Marto et al [70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124] incorporated an anti-inflammatory drug in starch-shelled nanoparticles by emulsion solvent evaporation method. The potential effectiveness of such topical formulation was evaluated both in vitro and in vivo on ra...…”
Section: Pharmaceutical Nanocarriers For Dermatological Applicationsmentioning
confidence: 99%
“…Any perturbance of this well-orchestrated balance can represent a strategy to perform an effective drug delivery through the skin by enhancing the permeation of active compounds through this desirable route [ 44 ]. Skin penetration can be enhanced by interaction with lipids, either by fluidizing or disorganizing lipids, and even extracting them; by interacting with proteins; and by increasing drug solubility and partitioning in the skin [ 45 , 46 , 47 ]. These phenomena are particularly achievable with the use of chemical penetration enhancers, such as terpenes, terpenoids, and essential oils [ 48 ].…”
Section: Introductionmentioning
confidence: 99%